Influence Mechanism of Osteopontin on Renal Injury in Patients with hereditary hypercalcemia by Enzyme-linked immunosorbent assay: Influence Mechanism of Osteopontin in Renal Injury - Peng, Yufang; Peng, Huiting; Ke, Wenbo (Cellular and Molecular Biology, 2023)
This study was to investigate the role and mechanism of osteopontin(OPN) in renal injury in patients with inherited hypercalciuria-bearing urinary calculi. The genetic hypercalcemia urolithiasis (GHS) rat model was established, and GHS rats were set as the experimental group (12 cases) and normal SD rats as the control group (12 cases). OPN and calcification levels in the kidney tissues of the two groups were compared by ELISA. According to calcium intervention or not, GHS rats were rolled into an intervention group (the intervention group was divided into 0.2g/L group, 0.4g/L group, and 0.7g/L group regarding the calcium injection dose, each group with 2 cases) and a normal group, each group with 6 cases. The levels of OPN and kidney injury in the two groups after 5h, 20h, and 40h were compared. Seventy patients with idiopathic hypercalciuria (IH) were rolled into a control group (injected with normal saline) and an observation group (injected with saline and OPN). The levels of OPN and calcification in kidney tissue of GHS rats in the experimental group were higher than those in the control group (P<0.05). The OPN level of GHS rats in the 0.2g/L group, 0.4g/L group, and 0.7g/L group was higher than that in the intervention group, and the OPN level at 5h, 10h, and 20h showed an upward trend (P<0.05). The incidence of renal injury in the intervention group (100%) was higher than that in the non-intervention group (16.67%) (P<0.05). Clinical verification results showed that urinary calcium excretion of IH patients in the observation group significantly decreased at 6 and 12 days, with statistical significance (P<0.05). The high probability of overactivation of OPN was one of the pathogeneses of hypercalciuria and calcium-bearing urolithiasis. The results suggested that OPN was closely related to the formation of urinary calculi and may cause certain damage to the kidney, which may be a key step in the prevention and treatment of urinary calculi.